Perancangan Dashboard Untuk Pemantauan Jumlah Siswa Pada PT XYZ Menggunakan Metode Prototyping - Shela,; Tony,; Dolok Lauro, Manatap (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
The development of technology has encouraged the growth of coding courses as a solution to prepare children for an increasingly digital future. PT XYZ is a course school that offers coding learning for children aged 5-18 years. Currently, PT XYZ already has several branches in major cities. In monitoring the number of students at each branch, PT XYZ still manages data manually which is vulnerable to inaccurate data. This research aims to design a dashboard that can be used to help companies monitor the number of students and other indicators related to company performance. This dashboard design uses the prototyping method and Microsoft Power BI. The result of this research is a dashboard system that can be used to monitor the number of students from the three main branches of PT XYZ, as well as display other information related to students that can help companies to set targets to be achieved.